Goniurosaurus wangshu sp. nov., a new species of Tiger Gecko from Guangdong, China (Squamata: Eublepharidae) - Zhu, Xiao-Yu; Wu, Shi-Yang; Liu, Yi-Jiao; Bai, Yun; Román-Palacios, Cristian; Li, Zheng; He, Zhu-Qing (Zootaxa, 2022)
A new species of Tiger Gecko in the genus Goniurosaurus is described from Guangdong, China. This new species, Goniurosaurus wangshu sp. nov. is the fifth species of Goniurosaurus found in karst topography of Guangdong. It is distinguished morphologically from congeners in this region by the combination of thirteen precloacal pores in male; dorsal ground color of head, body, and limbs in adults yellow; and iris orange. To validate our morphological inferences and support the description of Goniurosaurus wangshu sp. nov. as a new species, we sequenced 16S, CMOS, cytb, and RAG1 gene regions and performed molecular phylogenetic analyses. Phylogenetic analysis places the new species within the G. yingdeensis group and highlights the evolutionary distinction between this new species and other described congeners.